Impact of postoperative skin disinfection with chlorhexidine on bacterial colonisation following shoulder arthroplasty surgery: a controlled randomised study - Ida Markström; Karin Falk-Brynhildsen; Margareta Bachrack-Lindström; Gunilla Hollman Frisman; Sara Mernelius; Kristofer Bjerså (Elsevier, 2024)
Summary: Background: Surgical site infections are a significant threat to patient safety. Shoulder arthroplasty carries an increased risk due to foreign implants. Skin preparation in general is a key preoperative preventive intervention, and the use of chlorhexidine can have a prolonged effect on bacterial colonisation. There is a lack of evidence regarding whether postoperative disinfection has an impact on bacterial colonisation during the first 48 hours after surgery. Our hypothesis was that applying postoperative antiseptic with 5 mg/ml chlorhexidine in 70% ethanol would lead to reduced bacterial colonisation with Staphylococcus aureus, coagulase-negative staphylococcus and Cutibacterium acnes around the surgical wound within the initial 48 hours after elective shoulder surgery, compared with the use of sodium chloride. Methods: A single-blinded, controlled study was conducted at a county hospital in Sweden. Swabs from the skin were collected four times: at baseline, preoperatively, after the intervention and after 48 hours. Results: Our hypothesis was not confirmed. Although not statistically significant, the chlorhexidine group had a higher prevalence of bacterial colonisation of clinically relevant bacteria. Conclusions: Our study could not confirm that postoperative disinfection with chlorhexidine reduces bacterial colonisation compared with sodium chloride. The results highlight the complexity of SSIs and the importance of evidence-based preventive skin preparation to ensure patient safety. Further research is needed, considering the study's limitations, to explore and evaluate the effectiveness of different skin cleansing solutions and preventive strategies in diverse surgical contexts.